Measurement and Prediction of Railway Noise Case Study from Slovakia - Němec, Miroslav; Danihelová, Anna; Gergeľ, Tomáš; Gejdoš, Miloš; Ondrejka, Vojtěch; Danihelová, Zuzana (International journal of environmental research and public health, 2020)
The paper deals with comparing the measurement of noise from the railroads in the residential zone of the town of Zvolen with the results calculated using the prediction methods "Schall 03" (Deutsche Bundesbahn, 1990) and "Methodical instructions for the calculation of sound pressure level from transport" (MPVHD). The first is used in the Slovakia and second in the Czech Republic. The measurement results and the results obtained from the prediction methods for both measurement locations were evaluated graphically and statistically. The evaluation of the conformity of the measurement with the prediction showed that the results obtained using the method "Schall 03" are in better agreement with the measurement.
Keywords: železnice; monitorování životního prostředí; hluk dopravní; noise; rail transport; Slovakia; Railroads; Czech Republic; Environmental Monitoring; noise maps; prediction; Cities; velkoměsta; CadnaA; Noise, Transportation; Slovenská republika; Česká republika